2019
DOI: 10.1177/0033294119896062
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Admissions Interview: Piloting Multiple Mini-Interviews in a Graduate Psychology Program

Abstract: Health profession programs routinely utilize traditional interviews in admissions as a means of assessing important non-academic characteristics (e.g., critical thinking, interpersonal skills, judgment) of candidates. However, the reliability and validity of traditional interviews is highly questionable. Given this, multiple health profession programs (e.g., medicine, nursing, pharmacy, physical therapy) have implemented multiple mini-interviews as an alternative for assessing non-academic characteristics. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Some organizations have implemented strategies to hide applicant characteristics prior to interview selection to alleviate bias (e.g., racial bias; Government of Canada, 2018). To help improve the reliability and validity of interviews, programmes can standardize their interviews, use more than two raters, use diverse raters, calculate interrater reliabilities, and use these for discussion to improve decision-making (e.g., Clark et al, 2020; Kazmi et al, 2021). Additionally, these methods will need to be conducted from a standpoint of reducing racial bias in interview questions, such as the interviewer’s examination of their individual identity and how that could distort perceptions and lead to biases during the interview (Council of Chairs of Training Councils, 2020).…”
Section: Discussion: Potential Solutionsmentioning
confidence: 99%
“…Some organizations have implemented strategies to hide applicant characteristics prior to interview selection to alleviate bias (e.g., racial bias; Government of Canada, 2018). To help improve the reliability and validity of interviews, programmes can standardize their interviews, use more than two raters, use diverse raters, calculate interrater reliabilities, and use these for discussion to improve decision-making (e.g., Clark et al, 2020; Kazmi et al, 2021). Additionally, these methods will need to be conducted from a standpoint of reducing racial bias in interview questions, such as the interviewer’s examination of their individual identity and how that could distort perceptions and lead to biases during the interview (Council of Chairs of Training Councils, 2020).…”
Section: Discussion: Potential Solutionsmentioning
confidence: 99%
“…In Australia as well as internationally, entry into a professional training program in psychology leading to registration is an extremely competitive process with considerably more applicants each year than places. Therefore, significant responsibility is conferred on program staff to select the best candidates for training to become a psychologist (Clark, Miller and Garwood, 2019). As a duty of care to the profession and the public, those selected must be deemed suited to enter the profession.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may relate to the nature of the program being applied for and the information available to applicants before the interview. The impact of applicant diversity factors on MMI performance has also been examined (Clark, Miller and Garwood, 2019;Reiter and Eva, 2018). In their review, Reiter and Eva (2018) found variability in correlational findings across factors such as age, gender, cultural background, socioeconomic status, and rurality attributed to variations in MMI construction, content, and format, as well as differences in applicant pools and institutions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Strunk and Bailey (2015) reported from their empirical research that one-word changes (wife, partner, or husband in referring to one’s “significant other”) in the admission essay for graduate school changed the perception of the applicant. Clark and colleagues (2020) described a multiple mini-interview process that their graduate program implemented as part of the recruitment and selection process, and as they collected data about the efficacy of the multiple mini-interview process while using it, found strengths and weaknesses to the approach.…”
mentioning
confidence: 99%